Community pharmacists on the frontline in the chronic disease management: The need for primary healthcare policy reforms in low and middle income countries - Roland Nnaemeka Okoro; Sabina Onyinye Nduaguba (Elsevier, 2021)
In low- and middle-income countries (LMICs), over 12 million people die yearly from chronic diseases and this number is expected to increase if concerted actions are not taken. The purpose of this paper is to highlight the roles and impact of community pharmacists in chronic disease management support and the need for policymakers in LMICs to reposition community pharmacists appropriately for this extended role. Recent findings have shown that community pharmacists are the most accessible healthcare providers to the members of the community. Published evidence have demonstrated that community pharmacists' interventions in chronic diseases significantly improve economic, clinical, and humanistic outcomes. However, they are not officially recognized as primary healthcare providers in LMICs. Therefore, there is need for policy reforms that will encourage strategic use of the clinical skills of community pharmacists as part of the primary healthcare team in LMICs.